Communicative and Supportive Strategies: A Qualitative Study Investigating Nursing Staff's Communicative Practice With Patients With Aphasia in Stroke Care - Mia Ingerslev Loft; Cecilie Volck; Lise Randrup Jensen (SAGE Publishing, 2022)
This study aimed to provide detailed descriptions of the influences on the nursing staff's communicative practices with patients with aphasia in the context of usual stroke care interactions, and secondly to explore the nursing staff's use or non-use of supportive techniques, including the SCA TM method. A qualitative design was chosen, combining field observations and semi-structured interviews. Inductive and deductive qualitative content analysis was used. The results showed that the nursing staff's interactions with patients with aphasia were influenced by organizational and environmental influences, nurses' roles and functions and supporting patients with aphasia in communication. The role of the nursing staff in caring for the psychosocial well-being of patients is deprioritised in favor of other tasks. If there is no time or culture for prioritizing time for conversing with patients and supporting their psychosocial well-being, communication-partner training like SCA TM is likely hindered.